The Effect of the Principal’s Leadership Style and work Environment on the Performance of Madrasah Aliyah Teachers in East Sakra - Muh. Thahirul Hakim (Asshika: Journal of English Language Teaching and Learning, 2025)
The research aims to analyse the effects of leadership style and work environment on the performance of Madrasah Aliyah teachers in East Sakra. This study is quantitative. The sample in this study comprises 123 teachers from Madrasah Aliyah. The data analysis employed in this study was quantitative, which uses numerical data and statistical methods to test hypotheses. Multiple linear regressions were used in this study's statistical analysis. The results indicate that the principal’s leadership style, the work environment, and the performance of Madrasah Aliyah teachers in East Sakra are all rated as good. The principal's leadership style had a significant positive effect on the performance of Madrasah Aliyah teachers in East Sakra (p-value < 0.05). The work environment had a significant positive effect on the performance of Madrasah Aliyah teachers in East Sakra (p-value < 0.05). A madrasah principal was always a school leader whose primary role was to serve as a guiding force, influencing teachers and staff to undertake tasks that ensured a successful learning process. The work environment often expected in schools is one in which the school and its surroundings support teaching and learning in a healthy, relaxed, calm, and friendly manner.